Effect weight training on muscular hypertrophy: a systematic review - Ihsan, F.; Nasrulloh, A.; Nugroho, S.; Yuniana, R. (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. In the context of the growing importance of strength training, the analysis of the impact of strength loads on muscle hypertrophy becomes increasingly significant. Therefore, it is critical to comprehend both the effects of strength training on stimulating muscle growth and the potential ramifications. This study aimed to systematically analyze and collate the existing scientific evidence on the effects of weight training on muscle hypertrophy.